Adding Synonyms To A Concept In An Ontology - Herlina Jayadianti; Lukito Edi Nugroho; Paulus Insap Santosa; Wahyu Widayat; Carlos Alberta Baptista Sousa Pinto (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
The purpose of this paper is to provide research based understanding of adding sinonyms to a concept in an ontology. We hypothesize that managing synonyms with a good taxonomy and a good integration process are good approaches to organize and share knowledge. This paper can give a discourse to a group of people in different societies that want to share data using different concepts in the same domain. We will generate a common set of terms based on the terms of several different storage devices, used by different societies, in order to make data retrieval independent of the different perceptions and terminologies used by those societies. We use ontologies to represent the particular knowledge of each society and integration techniques to find relations between terms used in those ontologies.